EKSISTENSI DAN PEMERTAHANAN BAHASA BALI SEBAGAI BUDAYA LOKAL - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Balinese language can not only be reviewed in terms of linguistic aspects alone. Thereare three aspects in the Balinese language that form the core of its formation, namely aspects oflanguage, script, and literature that form the identity of Balinese culture itself. These threeaspects are the result of cultural mixing and reconstructed by Balinese ancestors into a culturalproduct that is closely related to the traditions of people's lives in Bali. In this paper, two problemstatements will be discussed as follows: (1) how is the existence of the Balinese language in thecontext of the preservation of Balinese culture? and (2) what forms of retention of local Balineseculture through Balinese language?In this brief study, it can be said that the existence of the Balinese language in relation to theform of local culture of the Balinese people is as the defense of their identity as Balinese with thecharacteristics of their activities and creativity which certainly cannot be separated from theuse of Balinese as a marker and cultural root, which is inseparable from the prevailing form oflanguage value, which is to upload Balinese bases which are still inherent in the language rulesof Balinese speakers. While the form of preserving the local culture of Balinese society throughthe Balinese language can be found in various aspects, namely on the religious aspects ofHinduism that are inseparable from the use of the Balinese language both in the form of language,scripts, and Balinese literature. Viewed from the aspect of the art of language wisdom, Balinesepeople will always survive because all aspects of Balinese art can not be separated from theBalinese language itself both in the fields of painting, music, architectural arts, sound arts(dance), dance, and drama/performance.